Probabilistic Safety Factor Assessment of Composite Pile Foundation Using Symmetrical FEM Reliability Method - Yi Wang; Guoyun Lu; Fenghui Dong (Buildings)
Composite pile foundation, as a new structural form in foundation engineering, has been widely used in the field of bridge engineering due to its overall superiority. This article focuses on the specific randomness problems encountered in the practical application of composite pile foundations, and uses probability based forward and backward reliability theory combined with finite element technology to study the safety of pile foundation structures. The safety of composite pile foundation structures needs to meet the requirements of established target reliability indicators while considering parameter randomness. The method proposed in this paper can verify whether it meets the established target reliability indicators while calculating the safety factor of composite pile foundations. This method has good operability. Through the engineering application and parameter sensitivity analysis of a specific case, the study shows that the variability of parameters has a significant impact on the calculation results of the probability safety factor, and the safety factor decreases with the increase in parameter variability. The target reliability index will also directly affect the value of the probability safety factor. The iterative initial value has no effect on the calculation results, indicating the applicability of the method proposed in this paper. The research results of this paper can provide theoretical and technical support for the safety design of composite pile foundations.